Quality of life and fertility preservation counseling for women with gynecological cancer: an integrated psychological and clinical perspective. (2nd April 2020) - La Rosa, Valentina Lucia; Shah, Mohsin; Kahramanoglu, Ilker; Cerentini, Taís Marques; Ciebiera, Michal; Lin, Li-Te; Dirnfeld, Martha; Minona, Patrizia; Tesarik, Jan
Abstract: Purpose: Relational and sexual problems are frequent in patients with a diagnosis of gynecological cancer, because this disease has a strong negative impact on female identity and sexuality. Psychological and sexual functioning is affected by inauspicious diagnosis. Furthermore, therapies may compromise reproductive function. The aim of this study is to propose a general overview on the impact of gynecological cancer on quality of life and psychological and sexual functioning, as well as on the importance of adequate counseling related to fertility preservation techniques. Materials and methods: We provide a narrative overview of the recent literature about quality of life and fertility preservation counselling in women with gynecological cancer. Results and conclusions: According to recent studies, 75% of women between 18 and 45 years with a diagnosis of cancer wish to have children. When cancer affects the reproductive system, the psychological distress is even stronger because there is a loss of menstrual function and fertility. Currently, fertility preservation techniques in women with gynecological cancer are beneficial and lead to an improvement in the quality of life.